Air‐Stable Organic Radicals: New‐Generation Materials for Flexible Electronics?. Issue 32 (25th June 2020) - Ji, Lei; Shi, Junqing; Wei, Juan; Yu, Tao; Huang, Wei
Abstract: In the last few years, air‐stable organic radicals and radical polymers have attracted tremendous attention due to their outstanding performance in flexible electronic devices, including transistors, batteries, light‐emitting diodes, thermoelectric and photothermal conversion devices, and among many others. The main issue of radicals from laboratory studies to real‐world applications is that the number of known air‐stable radicals is very limited, and the radicals that have been used as materials are even less. Here, the known and newly developed air‐stable organic radicals are summarized, generalizing the way of observing air‐stable radicals. The special electric and photophysical properties of organic radicals and radical polymers are interpreted, which give radicals a wide scope for various of potential applications. Finally, the exciting applications of radicals that have been achieved in flexible electronic devices are summarized. The aim herein is to highlight the recent achievements in radicals in chemistry, materials science, and flexible electronics, and further bridge the gap between these three disciplines. Abstract : Newly developed organic, air‐stable radicals and radical polymers, as well as their properties and applications in flexible electronic devices, are reviewed. Recently, these materials have shown high performance in batteries, photovoltaics, transistors, light‐emitting diodes, and photothermal devices. A short perspective is also given.